Extra-articular tenosynovial giant cell tumor of diffuse type in the temporal area with brain parenchymal invasion: a case report. (2nd November 2018) - Son, Seung-Myoung; Park, Young Seok; Choi, Chi-Hoon; Lee, Ho-Chang; Lee, Ok-Jun; Woo, Chang Gok
Abstract: Tenosynovial giant cell tumor of diffuse type is a locally aggressive neoplasm that most commonly arises in the lower extremities. Herein, we report for the first time a case of an extra-articular tenosynovial giant cell tumor of diffuse type in the temporal region with brain parenchymal invasion. Imaging studies revealed an intracranial expansile mass in the temporal bone without involvement of the temporomandibular joint. The unusual location of the tumor without involvement of the joint and the presence of brain parenchymal invasion made this case challenging to diagnose.